Humanism Investment Decisions: The Role Of Financial Attitude Through Financial Behavior Among Academics - Yusri Karmila; Eny Suprapti; Dina Amalya Putri (Sharia Economic and Management Business Journal (SEMBJ), 2026)
Background: Investment decisions in the modern era no longer focus solely on financial gains but also require consideration of ethical, social, and humanitarian values. Although financial literacy continues to improve, there remains a gap in understanding how humanistic values rooted in religion are internalized in investment decisions, particularly among academics who play a strategic role as agents of social change. The suboptimal role of financial attitudes and behaviors in bridging these values highlights the need to examine deeper mechanisms. Therefore, this research is important to contribute to the development of an investment decision-making model that is not only economically rational but also ethical and oriented toward social welfare. Method: This quantitative study examines the influence of humanism on academics’ investment decisions, with financial attitudes and financial behavior serving as mediating variables. Data were collected via a questionnaire from academics in Makassar who have investment experience. The sampling technique used was purposive sampling. This study employed a quantitative method using a survey approach involving 99 respondents who were lecturers at private universities in Makassar. Data were collected using a questionnaire with a 1–5 Likert scale and analyzed using the Partial Least Squares-Structural Equation Modeling (PLS-SEM) method via SmartPLS version 4.0 software and a structural model to test the research hypotheses. Results: 1) Financial attitudes have a significant positive effect on humanism in investment decision-making (p-value 0.000 < 0.10). 2) Financial attitudes have a significant positive effect on financial behavior (p-value 0.000 < 0.10). 3) Financial behavior has a significant positive effect on humanism in investment decision-making (p-value 0.092 < 0.10). 4) Financial attitude has a positive but insignificant effect on humanism in investment decision-making through financial behavior (p-value 0.121 > 0.10). Conclusion: Research shows that financial attitudes play a significant role in shaping humanistic investment decisions among academics. Positive financial attitudes were found not only to have a direct impact on humanistic investment orientation but also to encourage more disciplined and planned financial behavior. Sound financial behavior involves selecting investments that take into account humanistic values, ethics, and sustainability. However, the lack of significance does not directly indicate that the process of transformation from financial attitudes to behavior, and ultimately to humanistic investment decisions, is not yet consistent or optimal.